SOSIALISASI PENGENALAN VARIAN BARU VIRUS COVID-19 (OMICRON) GUNA MENINGKATKAN KESADARAN MASYARAKAT TENTANG PENTINGNYA VAKSINASI COVID-19 - Andi Khairul Musyawir; Imtihana Imtihana; Dewi Febrianti; Nober Pasiga; Dian Putri (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The virus that causes COVID-19, SARS-CoV-2 continues to undergo mutations forming new variants. The latest variant that has been detected, namely the Omicron variant known as the B.1.1.529 variant.  The Omicron variant has a high transmission rate of up to 5 times that of the previous variant including the Delta variant. The speed of transmission that occurs in South Africa is still being carried out epidemiological studies to find out whether this is caused by Omicron or other factors. Transmission is easier to occur in individuals who have not received the vaccine and this can also cause complications in their treatment. Nonetheless, some countries are concerned about pressure on health systems due to the increased need for hospitalizations as the rate of transmission of this variant is much higher. Viral replication occurs 70 times faster in the respiratory tract, but 10 times slower when in human lung tissue.  Because one of the efforts that can be done to avoid Covid-19 is to use a vaccine, it can help protect people around from the corona virus. Especially people who are at high risk of severe illness from COVID-19. By seeing these problems, it is necessary to have health counseling in getting to know the new variant of Covid-19 (omicron) and increasing public awareness of how important Covid-19 vaccination is